In vitro responses of dracaena fragrans cv. massangeana to growth regulators - Abdul Aziz, Maheran; Ooi, H. L.; Abdul Rashid, Azmi (Universiti Putra Malaysia Press, 1996)
In vitro studies on Dracaena fragrans cv. Massangeana revealed that young stem segments were capable of proliferating shoots on agar-solidified Murashige and Skoog (MS) basal medium containing different combinations and concentrations of BAP and NAA. Highest percentage of explants forming shoots was obtained on medium supplemented with 3.0 mgll BAP and 0.1 mgll NAA. The highest number ofshoots per explant occurred on medium containing 2.0 mgll BAP only. Highest percentage of callus formation and highest mean fresh weight of callus from young stem segments were achieved on MS medium supplemented with 1.0 mgll2,4-D. Adventitious rooting occurred after transferring excised shoots onto a hormone-free MS medium. Rooting was 100% for shoots derived from media with 0-2.0 mg/l BAP and a relatively low concentration of NAA (0.1 mg/l).